The Influence of Grammarly towards Indonesian EFL Students’ First-Degree Thesis Writing Confidence - Setyani, Erin Dwi; Bunau, Eusabinus; Rezeki, Yanti Sri (Elsya : Journal of English Language Studies, 2023)
Students completing their studies in the English Education Study Program must be required by thesis writing and submission. It was also acknowledged that the supervisors had afforded proper supervision. Nevertheless, for the English structure of the thesis writing correctness, it still needed help from an application, Grammarly. Therefore, this research aimed to describe the research participant’s engagement and how the application has influenced confidence in writing a thesis, and the confidence is exposed as a case to picture out. To determine which students worked using the application to write their thesis, a questionnaire was distributed to forty students enrolling in the ninth semester of the academic year 2019/2020. The result of the determination found twenty-nine students using the application to refine their writing subjects, and three of them working on their thesis writing completion under supervision using premium Grammarly were selected as the participants for this research. The selection criteria were on the basis of positive attitudes towards Grammarly, working on the thesis writing completion, and possessing a premium Grammarly account. The data of this research were participants’ error types collected from the thesis draft reviewed and their revision, and their opinion of the engagement and influence of Grammarly on writing confidence resulted from the interview. This research revealed that the participant’s thesis writing confidence was influenced by Grammarly diversity. Despite that diversity, as the case, this research inferred that the participants have positive emotions and attitudes in using Grammarly. The implication of this research is the promotion number of Grammarly users in the first-degree study program to make the supervision faster and the thesis writing better.